2012
DOI: 10.1089/neu.2011.1942
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Ameliorates Neurodegeneration, Suppresses Neuroinflammation, and Improves Behavioral Performance in a Mouse Model of Traumatic Brain Injury

Abstract: Although traumatic brain injury (TBI) is recognized as one of the leading causes of death from trauma to the central nervous system (CNS), no known treatment effectively mitigates its effects. Lithium, a primary drug for the treatment of bipolar disorder, has been known to have neuroprotective effects in various neurodegenerative conditions such as stroke. Until this study, however, it has not been investigated as a post-insult treatment for TBI. To evaluate whether lithium could have beneficial effects follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 59 publications
6
120
1
2
Order By: Relevance
“…28 Cells were seeded on glass cover slips at a density of 125,000/cm 2 and incubated under standard cell culture conditions in a humidified atmosphere at 5% CO 2 . Oxygen-glucose deprivation (OGD) was induced by transferring cells to Sterofundin medium (Braun, Germany) containing 1 mM mannitol and incubated at 37 C in a hypoxic chamber (1% O 2 , 5% CO 2 , remainder N 2 ) for 45 min with subsequent re-incubation under standard cell culture conditions for 24 h. Treatment with lithium (1 mM) was done 24 h before OGD and repeated at the beginning of reoxygenation.…”
Section: Preparation Of Cultured Neurons and Oxygen-glucose Deprivationmentioning
confidence: 99%
“…28 Cells were seeded on glass cover slips at a density of 125,000/cm 2 and incubated under standard cell culture conditions in a humidified atmosphere at 5% CO 2 . Oxygen-glucose deprivation (OGD) was induced by transferring cells to Sterofundin medium (Braun, Germany) containing 1 mM mannitol and incubated at 37 C in a hypoxic chamber (1% O 2 , 5% CO 2 , remainder N 2 ) for 45 min with subsequent re-incubation under standard cell culture conditions for 24 h. Treatment with lithium (1 mM) was done 24 h before OGD and repeated at the beginning of reoxygenation.…”
Section: Preparation Of Cultured Neurons and Oxygen-glucose Deprivationmentioning
confidence: 99%
“…58 Mild or severe traumatic brain injury induces hyperactivity in male and female mice Significant hyperactive exploration in the OF is a frequently reported effect of CCI delivered over parietal cortex in mice. 33,[59][60][61][62][63] In the current experiment, hyperactivity in injured mice ( Fig. 2A,B) was the result of more-continuous exploration in mice with TBI (fewer starts and stops; Fig.…”
Section: Females Are More Active During the First Exposure To Open Fieldmentioning
confidence: 53%
“…3C,D), corroborating previous findings in C57BL/6 mice when tested in an OF after parietal CCI. 33,59,62 However, testing of anxiety in the classic elevated plus maze (EPM) post-TBI yields disparate results. Washington and colleagues 72 reported that cortically injured mice spent a greater amount of time in anxiogenic regions of the EPM on the 20th day postinjury and concluded that brain injury results in increased ''risk-taking'' behaviors in mice.…”
Section: Severe Traumatic Brain Injury Induces Anxiety Equally In Malmentioning
confidence: 99%
“…10,11,[13][14][15][16][17]111,[115][116][117][119][120][121] These deficits, as reviewed in Osier and colleagues 122 and Thompson and coworkers, 123 can exceed those seen in our model, match them, or be more transient, depending on the severity of the impact. 10,11,124 For example, one of the least severe of these approaches, mild midline fluid percussion 1.4 atmosphere impact to the dura, produces TBI with little or no contusive injury to the brain, but causes optic nerve damage, similar to that in our TBI model. [125][126][127] Nonetheless, mild midline fluid percussion involves an open skull injury and thus does not mimic mild TBI in humans.…”
Section: Discussionmentioning
confidence: 71%